216k views
4 votes
3(5x+2)=2(3x-6)
help i need to show work and I have no idea how to do this

2 Answers

1 vote
The answer is -2. Below are the steps.
3(5x+2)=2(3x-6) help i need to show work and I have no idea how to do this-example-1
User Ezze
by
5.8k points
4 votes

Answer: its −2

Explanation:

3*(5*x+2)-(2*(3*x-6))=0

Step by step solution :

STEP

1

:

STEP

2

:

Pulling out like terms

2.1 Pull out like factors :

3x - 6 = 3 • (x - 2)

Equation at the end of step

2

:

(3 • (5x + 2)) - 6 • (x - 2) = 0

STEP

3

:

Equation at the end of step 3

3 • (5x + 2) - 6 • (x - 2) = 0

STEP

4

:

STEP

5

:

Pulling out like terms

5.1 Pull out like factors :

9x + 18 = 9 • (x + 2)

Equation at the end of step

5

:

9 • (x + 2) = 0

STEP

6

:

Equations which are never true

6.1 Solve : 9 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation:

6.2 Solve : x+2 = 0

Subtract 2 from both sides of the equation :

x = -2

One solution was found :

x = -2

User Shams Sujon
by
5.1k points